DIVERSITY OF MACROMOTHS (LEPIDOPTERA: HETEROCERA) IN PERLIS STATE PARK, KEDAWI REGION, MALAYSIA: NEW DISTRIBUTIONAL RECORD OF NOCTUID - Muhamad Ikhwan, Idris; Inda Mastura, ruslan; Christharina, Saurin Gintoron; Raziman, Imam Ghazali (Universiti Kebangsaan Malaysia, 2021)
This study aimed to determine the macromoths species diversity in Perlis State Park, Kedawi Region, Malaysia. Two sampling series were conducted on 17th - 21st April 2015 and 12th - 16th November 2015. Modified Pennsylvanian light trap with 160 W mercury vapor bulb was used to attract the macromoths in ground (≤ 2m) and lower canopy (≥ 20m) levels. A total of 386 individuals comprising 182 species from 13 families were recorded in 10 nights of sampling. The macromoths diversity was considerably high with Fisher’s alpha diversity index of α= 134.5 and Shannon’s diversity index, H’ = 4.777. Noctuidae was the highest family recorded in terms of species number, while family Arctiidae was the highest for the number of individuals collected.